CDKN1A Gene Expression in Two Multiple Myeloma Cell Lines With Different P53 Functionality - Drozdkova, Denisa Hrckova; Gursky, Jan; Minarik, Jiri; Überall, Ivo; Kolar, Zdenek; Trtkova, Katerina Smesny (Anticancer research, 2020)
BACKGROUND/AIM: Multiple myeloma is a highly heterogeneous disease of clonal plasma cells. Histone deacetylase (HDAC) inhibitors are promising anticancer drugs but their precise mechanisms of actions are not well understood. MATERIALS AND METHODS: Cell-cycle regulation and pro-apoptotic effects of two histone deacetylase inhibitors, suberohydroxamic acid (SAHA) and suberoylanilide hydroxamic acid (SBHA), were analyzed in multiple myeloma cell lines RPMI8226 and U266 with differing TP53 status using gene-expression analysis. RESULTS: Enhanced expression of cyclin-dependent kinase inhibitor 1A (CDKN1A/p21WAF/CIP1) detected in the TP53-deleted U266 cell line after SAHA treatment indicates the P53-independent mode of transcriptional activation of CDKN1A gene. In contrast, CDKN1A gene expression was significantly increased by both SBHA and SAHA treatment of TP53-mutated RPMI8226 cells. CONCLUSION: SAHA appears to be a potentially effective pro-apoptotic and anticancer drug with universal application in the treatment of heterogeneous populations of multiple myeloma cells.
Keywords: regulace genové exprese u nádorů; Tumor Suppressor Protein p53; Cyclin-Dependent Kinase Inhibitor p21; apoptóza; Cell Line, Tumor; Apoptosis; inhibitory histondeacetylas; Gene Expression Regulation, Neoplastic; lidé; Cell Cycle Checkpoints; kontrolní body buněčného cyklu; Antineoplastic Agents; protinádorové látky; mnohočetný myelom; Hydroxamic Acids; Histone Deacetylase Inhibitors; kyseliny hydroxamové; inhibitor p21 cyklin-dependentní kinasy; nádorový supresorový protein p53; Multiple Myeloma; Cell Survival; viabilita buněk; nádorové buněčné linie; Humans